Formation of Plant Microbiomes. Hypotheses and Controversies - Volkohon, V.V.; Shevchenko, L.A.; Волкогон, В.В.; Шевченко, Л.А. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Microorganisms play a key role in promoting plant growth, facilitating the assimilation of biogenic element compounds, increasing resistance to biogenic and abiogenic stress factors. The vast majority of researchers believe that the source of rhizosphere and endophytic microorganisms is the soil (horizontal provision hypothesis). At the same time, today there is growing interest in the concept of the formation of the plant microbiome as a result of heredity (vertical provision рнзщеруіші). A significant number of publications indicate that seed endophytic microorganisms may play a major role in this process. The presented literature review considers existing points of view on the processes of plant microbiome assembly with an emphasis on the importance of seed endophytes.